Analysis of a Diimine‐Organonickel Redox Series. Issue 31 (28th July 2020) - Sondermann, Christina; Pižl, Martin; Paretzki, Alexa; Feil, Christoph; Ringenberg, Mark R.; Záliš, Stanislav; Kaim, Wolfgang
Abstract : Complex cations [Ni(C5 R5 )(L)] +, L = 1, 4‐diphenyl‐2, 3‐dimethyl‐1, 4‐diaza‐1, 3‐butadiene, were compared as structurally characterized BF4 – (R = H) and SbF6 – salts (R = Me). These Ni II (L 0 ) compounds are reversibly reduced (R = H, Me) or oxidized (R = Me) and their one‐electron oxidized and reduced forms studied by EPR and UV/Vis spectroelectrochemistry, supported by DFT calculations. Surprisingly similar EPR features were observed for [Ni(C5 Me5 )(L)] 0 and [Ni(C5 Me5 )(L)] 2+ . Whereas the oxidation is largely metal centered to yield a Ni III species (R = Me), the reduction reveals energetically close‐lying alternatives (redox isomers) Ni I (L 0 ) and Ni II (L · – ). Abstract : A rare case of innocent α‐diimine ligand behavior and mostly metal‐based electron transfer has been evidenced for [Ni(C5 Me5 )(L)] n, n = 0, +, 2+, and L = 1, 4‐diphenyl‐2, 3‐dimethyl‐1, 4‐diaza‐1, 3‐butadiene via spectroelectrochemistry and DFT.